The Effect of Risk Management, Risk Mitigation, Auditor Reputation, Company Size, and Public Owned Shares on Underpricing - Victoria Ari Palma Akadiati; Einde Evana; Agrianti Komalasari (Institut Bisnis dan Informatika Kesatuan, 2026)
The information asymmetry in this study is proxied through the underpricing phenomenon that occurs when the company conducts an initial share price offering. This study aims to analyze and test the influence of risk management, risk mitigation, the reputation of public accounting firms, company size, and publicly owned shares on information asymmetry. This study uses a quantitative method on initial public offerings firms listed on the Indonesia Stock Exchange, analyzed with multiple linear regression and robustness checks using SPSS. The test results showed that risk mitigation and public accounting firms’ reporting had a significant negative influence on underpricing. This shows that these two variables act as signals of effective company quality. Information about risk mitigation is more acceptable to the market than information about risk identification alone. Risk management and company size show significant positive influences. This suggests that the market has an unnatural reaction to risk disclosures in large companies. In contrast to the variable of publicly owned stocks, which do not show a significant influence on underpricing. This research contributes by differentiating the roles of risk disclosure and risk management/mitigation and shows that investors respond more strongly to risk mitigation actions than to mere risk information.